L-RCA (ligation-rolling circle amplification): a general method for genotyping of single nucleotide polymorphisms (SNPs) - Qi, Xiaoquan (Oxford University Press, 2001)
A flexible, non-gel-based single nucleotide polymorphism (SNP) detection method is described. The method adopts thermostable ligation for allele discrimination and rolling circle amplification (RCA) for signal enhancement. Clear allelic discrimination was achieved after staining of the final reaction mixtures with Cybr-Gold and visualisation by UV illumination. The use of a compatible buffer system for all enzymes allows the reaction to be initiated and detected in the same tube or microplate well, so that the experiment can be scaled up easily for high-throughput detection. Only a small amount of DNA (i.e. 50 ng) is required per assay, and use of carefully designed short padlock probes coupled with generic primers and probes make the SNP detection cost effective. Biallelic assay by hybridisation of the RCA products with fluorescence dye-labelled probes is demonstrated, indicating that ligation-RCA (L-RCA) has potential for multiplexed assays.